Extraction of Natural Dyes from Palm’s Empty Fruit Bunches and Their Application on Cotton Fabric - Wusana Agung Wibowo (Waste Technology, 2017)
Natural dyes was extracted from palm’s empty fruit bunches (PEFB) by water extraction and applied for cotton fabric dyeing. The extracted dyes was characterized by liquid mass spectrometry and dyed cotton fabric was characterized by color fastnest to laundering and rubbing tests. Experimental results showed that soxhlet extraction process of PEFB for 80 minutes yielded 13.8%bw of solid dyes to naturally-dried PEFB with 4.15%bw of tannins. Furthermore, production of natural dyes was carried out in a 500 ml flask by extracting 25 g of PEFB in 250 ml of water at 100oC for 120 minutes. Absorbance of extracted dyes was found to be 3.925 at λmax. Cotton fabric dyeing was conducted at room temperature for all steps and post-mordanted by using Alum. The colors of the dyed cotton fabrics were then measured and expressed according to CIELab color system. Furthermore, the color fastnest test results obtained by Stainning Scale and Grey Scale were found to be 4-5 by color differences of 2. These results showed that dyed cotton fabric give a good rank on color fastnest.